Pengaruh Kepercayaan, Online Customer Review, dan Diskon terhadap Keputusan Pembelian melalui Minat Beli sebagai Variabel Intervening Pengguna Gofood pada Aplikasi Gojek di Jakarta - Rana Dzakira; Nova Anggrainie (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The development of information technology is also growing rapidly. One of the sectors that is also affected is transportation. This study aims to analyze the Influence of Trust, Online Customer Reviews, and Discounts on Purchasing Decisions Through Purchase Intention where the Intervening Variable is Gofood users on the Gojek application. The analysis method is quantitative primary data, with the test stages of convergent validity, Discriminant validity, average variance extracted (AVE), R-Square, predictive relevance (Q2), F-Square, path coefficient, specific indirect effect. Data were obtained through a questionnaire instrument, with a total of 175 respondents, which were then tested using SmartPLS 4.0. The research findings show that the Trust and Discount variables partially influence Purchasing Decisions through Purchase Intention of Gofood users on the Gojek application. Meanwhile, the Online Customer Review variable does not partially influence Purchasing Decisions through Purchase Intention of Gofood users on the Gojek application.